Preparation method and application of bimetal organic framework composite fiber membrane
Co/Zn-MOF composite fiber membranes are prepared through electrospinning technology and secondary growth method, which solves the problem of waste and uneven distribution of MOFs materials in the water treatment field, and achieves efficient dye removal and antibacterial properties, which are suitable for industrial pollution. Governance.
Patent Information
- Application Number
- CN202310706576.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the application of metal organic frame (MOFs) materials in the field of water treatment is limited by the waste of resources and difficulty in recycling caused by their powder form. In addition, traditional preparation methods have uneven distribution of MOFs particles on the fiber surface and pores. Congestion and other problems.
PAN nanofiber membrane was prepared by electrospinning technology, and Co/Zn-MOF crystal nuclei were formed on the fiber surface by secondary growth method. 2-MIM was used as an organic ligand to form coordination bonds with metal ions to control the lattice of MOF With structure and pore size, a bimetallic organic frame composite fiber membrane was prepared.
The removal rate of common anionic dyes is achieved by more than 80% and the antibacterial rate of E. coli and Staphylococcus aureus is 99.5% and 99.8%. It has excellent adsorption performance and antibacterial properties, and the preparation method is simple and the composite membrane is cost-effective. , suitable for industrial pollution control.
Smart Images

Figure CN119162734A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental functional materials, and in particular relates to a preparation method and application of a bimetallic organic framework composite fiber membrane. Background Art
[0002] With the rapid development of nanotechnology, the preparation of electrospun nanofibers has received more and more attention. Electrospun nanofiber membranes play an important role in many fields due to their high specific surface area, high porosity and good functionality. Especially in the field of wastewater treatment, electrospun fiber membranes solve the shortcomings of traditional methods such as high energy consumption, low efficiency and difficulty in recycling.
[0003] Metal-Organic Frameworks (MOFs) are porous materials connected by metal ions and organic ligands. They are widely used in antibacterial, drug delivery, adsorption, catalysis, etc. due to their various crystal structures, rich porosity, adjustable functions, inherent biodegradability and good biocompatibility. They can also be used for water remediation of organic pollutants. Most MOFs materials exist in the form of powders, which are not only difficult to recycle but also cannot be recycled, which easily leads to waste of resources and even damages the ecological environment, resulting in limited practical application in the field of water treatment. Therefore, combining MOFs nanoparticles with electrospun fiber membranes can effectively solve the above problems.
[0004] The blending method is the simplest and most direct method for preparing MOFs composite fiber membranes. It has a fast preparation speed and can eventually obtain a MOFs composite fiber membrane with a complete loaded crystal structure. However, there are problems such as uneven distribution of MOFs particles on the fiber surface, coverage by polymers, and fiber deformation. The in-situ growth method dissolves metal salts and organic ligands in an appropriate solvent and then generates MOFs particles on the fiber surface. This method solves the problems of poor dispersibility of MOFs in the polymer matrix and pore blockage in the blending method. CN 112853759 A discloses a metal organic framework core-shell fiber material and a preparation method thereof. MOFs particles are wrapped on the surface of nanofiber materials to make metal organic framework core-shell fiber materials, which not only retains the pore structure of nanofibers, but also increases the specific surface area of the composite fiber membrane. However, the premise of using this method is that the surface of the electrospun fiber contains enough active sites, otherwise the MOFs nanoparticles can grow on the surface of the nanofibers or around the nanofibers, which will lead to the loss of precursors and reduce the loading amount of MOFs on the surface of the nanofibers. The secondary growth method separates the MOFs nucleation and growth steps. Compared with the in-situ growth method, it is less likely to produce defective MOFs composite membranes and it is easier to control the microstructure of the membrane. A study (J. Mater. Chem., 2012, 22 (33): 16971-16978) first reported this new strategy, electrospinning a mixed solution of polystyrene with HKUST-1 and ZIF-8 to use it as a MOFs nucleus for secondary growth. Lu et al. (ACS Appl. Mater: Interfaces, 2017, 9 (15): 13632-13636) used the secondary growth method to prepare UiO-66-NH2 / PAN nanofiber composite materials for removing toxic chemicals. The MOFs composite fiber membrane prepared by this method solves the problems of MOFs nucleation density and grain uniformity to a certain extent, but the growth process is relatively complicated. Therefore, it is of great practical significance to further develop a MOFs composite fiber membrane material with simple operation and mild conditions, and a composite membrane with high cost performance, good stability and multifunctionality. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for preparing a bimetallic organic framework composite fiber membrane in view of the shortcomings of the prior art. The obtained cobalt-zinc bimetallic organic framework (Co / Zn-MOFs) composite membrane has a removal rate of more than 80% for a common anionic dye (sunset yellow) solution, and an antibacterial rate of 99.5% and 99.8% for Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus), respectively, with excellent adsorption performance, antibacterial property and reusability. The preparation method involved is simple, the composite membrane has a high cost-effectiveness, and has important application prospects in the fields of industrial pollution control.
[0006] To this end, the technical solution of the present invention is as follows:
[0007] A preparation method and application of a bimetallic organic framework composite fiber membrane, comprising the following steps:
[0008] 1) Preparation of PAN nanofiber membrane: PAN, organic ligand (2-methylimidazole, 2-MIM) and porogen are added to an organic solvent, stirred and mixed evenly at room temperature, and electrospun to obtain primary fibers. The primary fibers are soaked to remove the porogen, and then dried to obtain a PAN nanofiber membrane.
[0009] The porogen serves to increase the surface area of the fiber membrane, thereby increasing the active sites for MOF growth.
[0010] 2) Bimetallic MOF nucleus growth: The composite fiber membrane is placed in a mixed solution of bimetallic salts (cobalt acetate and zinc nitrate) with a concentration of 0.5 to 5 mol / L, and reacted at room temperature for 0.5 to 2 h to prepare a fiber membrane containing Co / Zn-MOF nuclei. The fiber membrane is rinsed three times with deionized water;
[0011] 3) Preparation of bimetallic MOF composite fiber membrane by secondary growth: The fiber membrane was then immersed in a 2-MIM solution of a certain concentration for 6 to 24 hours, rinsed with deionized water, and dried at 50°C to obtain a bimetallic MOF composite fiber membrane (Co / Zn-MOF@PAN).
[0012] The organic ligand 2-MIM has good solubility and stability, can form coordination bonds with metal ions, help the formation and crystal growth of MOF, improve the preparation efficiency and quality of MOF, and can control the lattice structure and pore size of MOF, so that it has better performance. The bimetallic MOF composite fiber membrane prepared by the secondary growth method has dense MOF particles.
[0013] Furthermore, the porogen in step 1) is ethanol, isopropanol, acetone, polyvinyl pyrrolidone, polyethylene glycol, zinc chloride or calcium carbonate.
[0014] Furthermore, the organic solvent in step 1) is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, or a mixed solvent thereof.
[0015] Furthermore, the conditions for electrospinning in step 1) are: voltage of 18-23 kV, receiving distance of 10-30 cm, spinning solution flow rate of 0.52 mL / h, spinning temperature of 20-30° C., humidity of 20-40%; and the needle used is a 19-23 gauge needle.
[0016] Furthermore, in step 2), the molar ratio of the bimetallic salt to the organic ligand is 3:1 to 1:3; the molar ratio between the bimetallic salts is 5:1 to 1:5.
[0017] Furthermore, the bimetallic salt in step 2) is copper nitrate, zirconium nitrate, nickel nitrate, ferric chloride, etc.
[0018] Furthermore, in step 3), the concentration of the organic ligand is 0.08 mol / L to 1.60 mol / L.
[0019] Furthermore, the organic ligand in step 3) is 2-ethylimidazole, 2-propylimidazole, 2-isopropylimidazole, 2-methylbenzimidazole, 2-methyl-4-ethylimidazole, 2-methyl-4-isopropylimidazole, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, etc.
[0020] Compared with the prior art, the technical solution provided by the present invention has the following advantages:
[0021] 1) Electrospinning technology is used to produce nanofibers with high porosity, high specific surface area and excellent surface hydrophilicity; 2) The bimetallic MOF composite fiber prepared by the secondary growth method can effectively increase the growth points of MOF on the fiber surface, and obtain a composite fiber membrane with a densely grown MOF layer on the surface; 3) The bimetallic MOF composite membrane has excellent dye adsorption performance, and the removal rate of the common anionic dye (sunset yellow) solution is more than 80%; 4) The antibacterial rate of the composite membrane against Escherichia coli and Staphylococcus aureus reaches 99.9%, with excellent antibacterial properties, achieving the purpose of efficient and safe treatment of industrial wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 a is the SEM image (×5000) of the PAN nanofiber membrane obtained in Example 1;
[0023] Figure 1 b is the SEM image (×15000) of the PAN nanofiber membrane obtained in Example 1;
[0024] Figure 1 c is the SEM image of Co / Zn-MOF@PAN0.02 nanofibers obtained in Example 2 (×10000);
[0025] Figure 1 d is the SEM image of Co / Zn-MOF@PAN0.08 nanofibers obtained in Example 3 (×10000);
[0026] Figure 1 e is the SEM image of Co / Zn-MOF@PAN0.16 nanofibers obtained in Example 4 (×10000);
[0027] Figure 2 XPS graphs of PAN obtained in Example 1 and Co / Zn-MOF@PAN0.08 nanofibers obtained in Example 3;
[0028] Figure 3 The antibacterial effects of the PAN nanofiber membrane prepared in Example 1 and the Co / Zn-MOF@PAN0.16 nanofiber membrane prepared in Example 4 after being cultured with E. coli and S. aureus for 24 hours respectively;
[0029] Figure 4 a is the isothermal adsorption curve of Co / Zn-MOF@PAN0.16 nanofiber membrane prepared in Example 4;
[0030] Figure 4 b is the Freundlich adsorption isotherm fitting diagram of Co / Zn-MOF@PAN0.16 nanofiber membrane prepared in Example 4. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0032] The adsorption performance experiment of PNA and Co / Zn-MOF@PAN nanofiber membranes prepared in some embodiments is carried out as follows:
[0033] ① The amount of sunset yellow (SY) solution used in the adsorption test was 30 mL. The adsorption process was carried out at 120 rpm in a constant temperature shaker at 35°C. SY solutions with initial concentrations of 20 mg / L, 50 mg / L, 100 mg / L, 150 mg / L, and 200 mg / L were prepared, and an equal amount of 100 mg of sample fiber membrane was added. The adsorption was carried out for 8 hours. After the adsorption was completed, an ultraviolet spectrophotometer was used to measure the absorbance at a wavelength of 483 nm, and the SY standard curve was used to measure the adsorption amount and removal rate of the sample.
[0034] ② Use two models, namely Langmuir and Freundlich models, to perform linear fitting on the adsorption data of the fiber membrane samples and compare them with the adsorption isotherm to explore the mode of action.
[0035] The antibacterial performance experiments were conducted on the PNA and Co / Zn-MOF@PAN nanofiber membranes prepared in some examples. The specific process is as follows:
[0036] ① Preparation of Luria-Bertani (LB) liquid medium and solid medium: 10g peptone, 5g yeast extract powder and 10g NaCl are fully dissolved in 1L distilled water, and the pH of the LB liquid medium is adjusted to 7.2-7.4 with NaOH solution. After sterilization in a 120℃ high-pressure steam sterilizer, place it in a clean bench for use. The preparation method of LB solid medium is to add 10g peptone, 5g yeast extract powder, 10g NaCl and 20g agar to 1L distilled water, heat in an 80℃ water bath to fully dissolve, and then sterilize in a 120℃ high-pressure steam sterilizer, pour it into a sterile culture dish in a clean bench and dry it naturally for use. E. coli and S. aureus were inoculated into 200mL LB liquid medium respectively, and the bacterial liquid concentration was fixed at 107~10 8 CFU / mL is reserved.
[0037] ② Plate count method
[0038] The antibacterial properties of Co / Zn-MOF@PAN nanofiber membranes were tested by plate counting method. First, 40 mg of sample was weighed, sterilized by ultraviolet irradiation, and added to phosphate buffer solution (PBS, pH = 7.4), and then bacterial suspension (concentration of 107-10 8 CFU / mL), and cultured in a constant temperature incubator at 37°C. Finally, the bacterial suspension cultured with the sample for 24 hours was selected, diluted step by step with sterile water, and 0.1 mL of each bacterial suspension with three different concentration gradients was selected to spread on a plate, and cultured in a constant temperature incubator at 37°C for 24 hours, and the antibacterial rate of each sample was calculated.
[0039] Example 1
[0040] A preparation method and application of a bimetallic organic framework composite fiber membrane, comprising the following steps:
[0041] Preparation of PAN nanofiber membrane: Weigh 1.76g PAN and add it to 10g DMF, stir for 10h to make a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to make PAN spinning solution. Load the spinning solution into a syringe and use an electrospinning machine to make PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%.
[0042] Depend on Figure 1 From a and b, it can be seen that the fiber diameter is uniform and the surface is smooth without any protrusions or grooves.
[0043] Depend on Figure 2 It can be seen that the binding energy of PAN fiber membrane corresponds to the XPS peaks of C1s, N1s and O1s at 284.9 eV, 399.1 eV and 532.1 eV, respectively.
[0044] Depend on Figure 3 As shown, PAN nanofiber membrane has no antibacterial effect.
[0045] Example 2
[0046] A preparation method and application of a bimetallic organic framework composite fiber membrane, comprising the following steps:
[0047] 1) Preparation of PAN nanofiber membrane: Weigh 1.76g PAN and 2-MIM and add them to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%.
[0048] 2) Bimetallic MOF nucleus growth: The composite fiber membrane was immersed in a mixed solution of Zn(NO3)2·6H2O and Co(AC)2·4H2O at a concentration of 0.1 mol / L for 2 h to prepare a fiber membrane containing Co / Zn-MOF nuclei. The fiber membrane was rinsed three times with deionized water.
[0049] 3) Preparation of bimetallic MOF composite fiber membrane by secondary growth: The fiber membrane was then immersed in 0.02 mol / L 2-MIM solution for reaction for 12 h, rinsed with deionized water, and dried at 50 °C to obtain a Co / Zn-MOF@PAN0.02 composite fiber membrane.
[0050] Figure 1 As shown in c, there are a small amount of Co / Zn-MOF nanoparticles on the surface of Co / Zn-MOF@PAN0.02 fiber membrane.
[0051] Example 3
[0052] A preparation method and application of a bimetallic organic framework composite fiber membrane, comprising the following steps:
[0053] 1) Preparation of PAN nanofiber membrane: Weigh 1.76g PAN and 2-MIM and add them to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cn, spinning time 4h, humidity <30%.
[0054] 2) Bimetallic MOF nucleus growth: The composite fiber membrane was immersed in a mixed solution of Zn(NO3)2·6H2O and Co(AC)2·4H2O at a concentration of 0.1 mol / L for 2 h to prepare a fiber membrane containing Co / Zn-MOF nuclei. The fiber membrane was rinsed three times with deionized water.
[0055] 3) Preparation of bimetallic MOF composite fiber membrane by secondary growth: The fiber membrane was then immersed in 0.08 mol / L 2-MIM solution for reaction for 12 h, rinsed with deionized water, and dried at 50 °C to obtain a Co / Zn-MOF@PAN0.08 composite fiber membrane.
[0056] Figure 1 As shown in d, Co / Zn-MOF nanoparticles on the surface of Co / Zn-MOF@PAN0.08 fiber membrane.
[0057] Depend on Figure 2 It can be seen that in addition to the XPS peaks of C1s, N1s and O1s on the Co / Zn-MOF@PAN0.08 spectrum, peaks of Co and Zn elements can also be observed, indicating that Co / Zn-MOF nanoparticles are successfully grown on the surface of PAN fibers.
[0058] Example 4
[0059] A preparation method and application of a bimetallic organic framework composite fiber membrane, comprising the following steps:
[0060] 1) Preparation of PAN nanofiber membrane: Weigh 1.76g PAN and 2-MIM and add them to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%.
[0061] 2) Bimetallic MOF nucleus growth: The composite fiber membrane was immersed in a mixed solution of Zn(NO3)2·6H2O and Co(AC)2·4H2O at a concentration of 0.1 mol / L for 2 h to prepare a fiber membrane containing Co / Zn-MOF nuclei. The fiber membrane was rinsed three times with deionized water.
[0062] 3) Preparation of bimetallic MOF composite fiber membrane by secondary growth: The fiber membrane was then immersed in 0.16 mol / L 2-MIM solution for reaction for 12 h, rinsed with deionized water, and dried at 50 °C to obtain a Co / Zn-MOF@PAN0.16 composite fiber membrane.
[0063] Figure 1As shown in d, Co / Zn-MOF nanoparticles on the surface of Co / Zn-MOF@PAN0.16 fiber membrane.
[0064] Depend on Figure 3 It can be seen that after the Co / Zn-MOF@PAN0.16 nanofiber membrane was cultured with the bacterial solution for 24 hours, the antibacterial rates of the fiber membrane against E. coli and S. aureus were 99.5% and 99.8%, respectively, indicating that the Co / Zn-MOF@PAN nanofiber membrane has excellent antibacterial properties.
[0065] Figure 4 As shown in a and b, the adsorption amount of Co / Zn-MOF@PAN0.16 fiber membrane gradually increases, and the fitting results are more consistent with the Freundlich model, proving that the adsorption process is multilayer adsorption, which has both physical adsorption and chemical adsorption.
[0066] Example 5
[0067] A preparation method and application of a bimetallic organic framework composite fiber membrane, comprising the following steps:
[0068] 1) Preparation of PAN nanofiber membrane: Weigh 1.76g PAN and 2-MIM and add them to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.15g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%.
[0069] 2) Bimetallic MOF nucleus growth: The composite fiber membrane was immersed in a mixed solution of Zn(NO3)2·6H2O and Co(AC)2·4H2O at a concentration of 0.1 mol / L for 2 h to prepare a fiber membrane containing Co / Zn-MOF nuclei. The fiber membrane was rinsed three times with deionized water.
[0070] 3) Preparation of bimetallic MOF composite fiber membrane by secondary growth: The fiber membrane was then immersed in 0.16 mol / L 2-MIM solution for reaction for 12 h, rinsed with deionized water, and dried at 50 °C to obtain a Co / Zn-MOF@PAN0.16 composite fiber membrane.
[0071] Example 6
[0072] A preparation method and application of a bimetallic organic framework composite fiber membrane, comprising the following steps:
[0073] 1) Preparation of PAN nanofiber membrane: Weigh 1.76g PAN and 2-MIM and add them to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g poly Z glycol and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution is loaded into a syringe and an electrospinning machine is used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%.
[0074] 2) Bimetallic MOF nucleus growth: The composite fiber membrane was immersed in a mixed solution of Zn(NO3)2·6H2O and Co(AC)2·4H2O at a concentration of 0.1 mol / L for 2 h to prepare a fiber membrane containing Co / Zn-MOF nuclei. The fiber membrane was rinsed three times with deionized water.
[0075] 3) Preparation of bimetallic MOF composite fiber membrane by secondary growth: The fiber membrane was then immersed in 0.16 mol / L 2-MIM solution for reaction for 12 h, rinsed with deionized water, and dried at 50 °C to obtain a Co / Zn-MOF@PAN0.16 composite fiber membrane.
[0076] Example 7
[0077] A preparation method and application of a bimetallic organic framework composite fiber membrane, comprising the following steps:
[0078] 1) Preparation of PAN nanofiber membrane: Weigh 1.76g PAN and 2-MIM and add them to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%.
[0079] 2) Bimetallic MOF nucleus growth: The composite fiber membrane was immersed in a mixed solution of 0.05 mol / L Zn(NO3)2·6H2O and 0.15 mol / L Co(AC)2·4H2O for 2 h to prepare a fiber membrane containing Co / Zn-MOF nuclei. The fiber membrane was rinsed three times with deionized water.
[0080] 3) Preparation of bimetallic MOF composite fiber membrane by secondary growth: The fiber membrane was then immersed in 0.16 mol / L 2-MIM solution for reaction for 12 h, rinsed with deionized water, and dried at 50 °C to obtain a Co / Zn-MOF@PAN0.16 composite fiber membrane.
[0081] Example 8
[0082] The 2-MIM in steps 1) and 3) of Example 4 was replaced by 2-methylbenzimidazole, and the other conditions were the same as those of Example 4.
[0083] Example 9
[0084] The 2-MIM in steps 1) and 3) of Example 4 was replaced by 2-ethylimidazole, and the other conditions were the same as those of Example 4.
[0085] Example 10
[0086] The polyethylene glycol in step 1) of Example 6 was replaced by zinc chloride, and the other conditions were the same as those of Example 6.
[0087] Embodiment 11
[0088] The polyethylene glycol in step 1) of Example 6 was replaced by calcium carbonate, and the other conditions were the same as those of Example 6.
[0089] Example 12
[0090] The concentration of the PAN spinning solution in step 1) of Example 7 was changed to a 10 wt % solution, and the other conditions were the same as those of Example 7.
[0091] Embodiment 13
[0092] The concentration of the PAN spinning solution in step 1) of Example 7 was changed to a 12 wt % solution, and the other conditions were the same as those of Example 7.
Claims
1. A preparation method and application of a bimetallic organic framework composite fiber membrane, characterized in that The steps include: 1) Preparation of PAN nanofiber membrane: PAN, organic ligand (2-methylimidazole, 2-MIM) and porogen are added to an organic solvent, stirred and mixed evenly at room temperature, and electrospun to obtain primary fibers. The primary fibers are soaked to remove the porogen, and then dried to obtain a PAN nanofiber membrane. 2) Bimetallic MOF nucleus growth: The composite fiber membrane is placed in a mixed solution of bimetallic salts (cobalt acetate and zinc nitrate) with a concentration of 0.5 to 5 mol / L, and reacted at room temperature for 0.5 to 2 h to prepare a fiber membrane containing Co / Zn-MOF nuclei. The fiber membrane is rinsed three times with deionized water; 3) Preparation of bimetallic MOF composite fiber membrane by secondary growth: The fiber membrane was then immersed in a 2-MIM solution of a certain concentration for 6 to 24 hours, rinsed with deionized water, and dried at 50°C to obtain a bimetallic MOF composite fiber membrane (Co / Zn-MOF@PAN). The organic ligand can form a coordination bond with the metal ion, help the formation and crystal growth of MOF, and control the lattice structure and pore size of MOF; the bimetallic MOF composite fiber membrane prepared by the secondary growth method has dense MOF particles.
2. The method for preparing a bimetallic organic framework composite fiber membrane according to claim 1, characterized in that: The porogen in step 1) is ethanol, isopropanol, acetone, polyvinyl pyrrolidone, polyethylene glycol, zinc chloride or calcium carbonate.
3. The method for preparing a bimetallic organic framework composite fiber membrane according to claim 1, characterized in that: The organic solvent in step 1) is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or a mixed solvent thereof.
4. The method for preparing a bimetallic organic framework composite fiber membrane according to claim 1, characterized in that: Step 1) The conditions for electrospinning are: voltage of 18-23 kV, receiving distance of 10-30 cm, spinning solution flow rate of 0.5-2 mL / h, spinning temperature of 20-30° C., humidity of 20-40%; the needle used is a 19-23 gauge needle.
5. The method for preparing a bimetallic organic framework composite fiber membrane according to claim 1, characterized in that: In step 2), the molar ratio of the bimetallic salt to the organic ligand is 3:1 to 1:3; the molar ratio between the bimetallic salts is 5:1 to 1:
5.
6. The method for preparing a bimetallic organic framework composite fiber membrane according to claim 1, characterized in that: The bimetallic salt in step 2) is copper nitrate, zirconium nitrate, nickel nitrate, ferric chloride, etc.
7. The method for preparing a bimetallic organic framework composite fiber membrane according to claim 1, characterized in that: In step 3), the concentration of the organic ligand is 0.08 mol / L to 1.60 mol / L.
8. The method for preparing a bimetallic organic framework composite fiber membrane according to claim 1, characterized in that: The organic ligand in step 3) is 2-ethylimidazole, 2-propylimidazole, 2-isopropylimidazole, 2-methylbenzimidazole, 2-methyl-4-ethylimidazole, 2-methyl-4-isopropylimidazole, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, etc.
Citation Information
Patent Citations
Metal organic framework core-shell fiber material and preparation method thereof
CN112853759A
Preparation method of PVP / PAN nano-composite fiber
CN107675281A
Preparation method of amino acid graft nanofiber membrane for bilirubin adsorption
CN108103662A
Preparation method and application of polydopamine modified ZIF-8 functionalized nanofiber membrane
CN109577005A
Metal organic framework ZIF-8 membrane, preparation method and application thereof
CN112717706A
Cited By
Flexible MOF (Metal Organic Framework) microfiltration membrane as well as preparation method and application thereof
CN119656868A
A flexible MOF microfiltration membrane, its preparation method and application
CN119656868B
Metal organic framework film, preparation method and application thereof
CN120695789A
A metal-organic framework membrane, its preparation method and its application
CN120695789B
